Stock prices and monetary policy : evidence from Malaysia case - Chin, Nyuk Fui (Universiti Malaysia Sarawak (UNIMAS), 2011)
Studies to determine the relationship between stock prices and monetary policy have long been pursued, however as Tobin (1969), Blanchard (1981) and Shah (1984) mentioned, there are still no any empirical study illustrated the best on how the interaction between the monetary policy and stock market as well as little effort has been place in identify the relation of these variables for emerging market especially Malaysia compare to the advanced market. This study explores empirically the integration between Malaysian stock prices and monetary policy in post-crisis as well as linkage with other macroeconomic variables. The study uses the Autoregressive Distributed Lag Model (ARDL), Variance Decomposition (VDCs) and Impulse Response Function (IRFs). The study finds that the stock prices and monetary policy has a bidirectional relation in short-run and long-run as consistent with Bjornland and Leitemo (2008). Moreover, the macroeconomics variables display a cointegration with stock prices and monetary policy. Astonishingly, Malaysian stock prices also have significant interaction with the federal fund rate. To the certain extent the market is informational inefficient, these findings make obvious evidence that are contradictory with Efficient Market Hypothesis (EMH).